Em nome da autonomia e do desenvolvimento: Brasil e a não-proliferação, o desarmamento e os usos pacíficos da energia nuclear - Jesus, Diego Santos Vieira de (2017)
The objective is to examine the positions adopted by Brazil on nuclear non-proliferation, disarmament and peaceful uses of nuclear energy in the beginning of this century. The central argument indicates that Brazil aims to pressure the nuclear-weapon states to fulfill their disarmament obligations, while seeks to preserve autonomy to develop peaceful nuclear activities.